andean and amazonian societies from the past: collective memory and history historicities - Arana Bustamante, Luis (2013)
It is attempted in this study to precise a preliminary set of concepts for an analysis of acquisition of historical sense by traditional societies of Andean and Amazonian areas in modern context and with reference to the school. The usual variety in the interpretation of facts by these societies is presented in its cultural context with a preliminary treatment of historicities and mythistory in these areas. In a first cross-cultural analysis of this way, it is made a somere comparation with some historicities of modern Peruvian society. It is also attempted an analytic differentiation of these historicities with the historiographical thought and historical conscience properly conceived. At the end, there are some reflections about a future construction of a historical narrative of this traditional societies with consideration of the somewhere elusive factors of perspective and transdisciplinarity.